Islam and modernity: a case of Muslim female engineers in Malaysia - Abd. Rokis, Rohaiza (International Islamic University Malaysia, 2011)
Malaysia is portrayed as one of the modern and developed Muslim nations. Its rapid modern development in physical structure impressed many people. However, little is known about the situation of its non-physical structure, particularly the religious and normative values. This paper rests on the stance that individuals’ religious values remain despite the nation’s effort towards modernisation, particularly in the relations of women and profession. To achieve the purpose, this article explores the paradoxes relating to the intricate relationships between the traditional feminine social expectations and modern engineering profession experienced by Muslim female engineers and students in Malaysia. The research is a structured interview design on thirty-six Muslim female engineers and engineering students. It found that there were potential self-presentation crises, particularly when women participated in a male-dominated workplace. The gendering issues in engineering overwhelmingly projected the collision between modernism and traditionalism. Such a blending situation depended on very careful management as being women with a clear expectation towards traditional feminine roles and responsibilities, while at the same time they have to present themselves in a business-like, modern manner in terms of competence, commitment and ambitious targets to claim a rightful place in the engineering world. Modernisation has not been able to change women’s traditional attitude. Though they may be modernised, educated and professional, these women are still traditional at heart.